Functional analysis of soybean cyst nematode-inducible synthetic promoters and their regulation by biotic and abiotic stimuli in transgenic soybean (Glycine max) - Sultana, Mst Shamira; Mazarei, Mitra; Millwood, Reginald J.; Liu, Wusheng; Hewezi, Tarek; Stewart, C. Neal (Frontiers in Plant Science, 2022)
We previously identified cis-regulatory motifs in the soybean (Glycine max) genome during interaction between soybean and soybean cyst nematode (SCN), Heterodera glycines. The regulatory motifs were used to develop synthetic promoters and their inducibility in response to SCN infection was shown in transgenic soybean hairy roots. Here, we studied the functionality of two SCN-inducible synthetic promoters (4×M1.1 and 4×M2.3) in whole transgenic soybean. Histochemical GUS analyses of transgenic soybean plants containing the individual synthetic promoter::GUS construct revealed that under unstressed condition, no GUS activity is present in leaves and roots. While upon nematode infection, the synthetic promoters direct GUS expression to roots predominantly in the nematode feeding structures induced by the SCN and by the root-knot nematode (RKN), Meloidogyne incognita. There were no differences in GUS activity in leaves between nematode-infected and non-infected plants. Furthermore, we examined the specificity of the synthetic promoters in response to various biotic (insect: fall armyworm, Spodoptera frugiperda; and bacteria: Pseudomonas syringe pv. glycinea, P. syringe pv. tomato, and P. marginalis) stresses. Additionally, we examined the specificity to various abiotic (dehydration, salt, cold, wounding) as well as to the signal molecules salicylic acid (SA), methyl jasmonate (MeJA), and abscisic acid (ABA) in the transgenic plants. Our wide-range analyses provide insights into the potential applications of synthetic promoter engineering for conditional expression of transgenes leading to transgenic crop development for resistance improvement in plant.